Autophagy in Plants – What's New on the Menu?. (February 2016) - Michaeli, Simon; Galili, Gad; Genschik, Pascal; Fernie, Alisdair R.; Avin-Wittenberg, Tamar
Abstract : Autophagy is a major cellular degradation pathway in eukaryotes. Recent studies have revealed the importance of autophagy in many aspects of plant life, including seedling establishment, plant development, stress resistance, metabolism, and reproduction. This is manifested by the dual ability of autophagy to execute bulk degradation under severe environmental conditions, while simultaneously to be highly selective in targeting specific compartments and protein complexes to regulate key cellular processes, even during favorable growth conditions. Delivery of cellular components to the vacuole enables their recycling, affecting the plant metabolome, especially under stress. Recent research in Arabidopsis has further unveiled fundamental mechanistic aspects in autophagy which may have relevance in non-plant systems. We review the most recent discoveries concerning autophagy in plants, touching upon all these aspects. Trends: Autophagy is involved in almost every aspect of plant life, including germination, seedling establishment, development, reproduction, metabolism, and stress tolerance. Proteins that are involved in fundamental processes of autophagy, such as autophagosome biogenesis, were recently characterized in plants. Autophagy is intimately associated with other intracellular trafficking pathways. Several selective autophagy pathways were recently identified in Arabidopsis ; most are common to all eukaryotes. Nevertheless, some pathways were initially discovered in plants and others are plant-specific. As an intracellular recycling system, autophagy is highly important for proper plant metabolism and nutrient allocation, both during stress and favorable growth conditions.